Population and development in Vietnam : (United Nations Population Fund in Vietnam (UNFPA), 2009)
The present report title " Population and Development in Vietnam: Towards a new strategy, 2011 - 2020" has been commissioned by UNFPA, and it aims to provide a thorough and comprehensive review and analysis of key population and development issues facing Vietnam in the years to come and, based on that, provide tentative recommendations to the Ministry of Health as it develops the new Strategy.